Eight new species of Amphinemura (Plecoptera: Nemouridae) from Vietnam - Stark, Bill P. (Illiesia, 2010)
Eight new species of Amphinemura are recognized based on specimens collected in Vietnam. New taxa include A. bifurcata sp. n., A. caoae sp. n., A. divergens sp. n., A. giay sp. n., A. meyi sp. n., A. sapa sp. n., A. tamdao sp.n. and A. viet sp. n. A single male specimen of A. gressitti Kawai and a male and female of A. hainana Li & Yang are also reported and two species based on unassociated females are described under informal designations. A preliminary key for males of Amphinemura known for Vietnam is presented.
Keywords: Amphinemura; entomology; Nemouridae; new species; Plecoptera; Vietnam